The Small RNA ErsA Impacts the Anaerobic Metabolism of Pseudomonas aeruginosa Through Post-Transcriptional Modulation of the Master Regulator Anr - Ferrara, Silvia; Carrubba, Riccardo; Santoro, Silvia; Bertoni, Giovanni (Frontiers in Microbiology, 2021)
Pseudomonas aeruginosa is one of the most critical opportunistic pathogens in humans, able to cause both lethal acute and chronic lung infections. In previous work, we indicated that the small RNA ErsA plays a role in the regulatory network of P. aeruginosa pathogenicity in airways infection. To give further insight into the lifestyle functions that could be either directly or indirectly regulated by ErsA during infection, we reanalyzed the categories of genes whose transcription appeared dysregulated in an ersA knock-out mutant of the P. aeruginosa PAO1 reference strain. This preliminary analysis indicated ErsA as a candidate co-modulator of denitrification and in general, the anaerobiosis response, a characteristic physiologic state of P. aeruginosa during chronic infection of the lung of cystic fibrosis (CF) patients. To explain the pattern of dysregulation of the anaerobic-lifestyle genes in the lack of ErsA, we postulated that ErsA regulation could target the expression of Anr, a well-known transcription factor that modulates a broad regulon of anoxia-responsive genes, and also Dnr, required for the transcription activation of the denitrification machinery. Our results show that ErsA positively regulates Anr expression at the post-transcriptional level while no direct ErsA-mediated regulatory effect on Dnr was observed. However, Dnr is transcriptionally down-regulated in the absence of ErsA and this is consistent with the well-characterized regulatory link between Anr and Dnr. Anr regulatory function is critical for P. aeruginosa anaerobic growth, both through denitrification and fermentation of arginine. Interestingly, we found that, differently from the laboratory strain PAO1, ErsA deletion strongly impairs the anaerobic growth by both denitrification and arginine fermentation of the RP73 clinical isolate, a multi-drug resistant P. aeruginosa CF-adapted strain. This suggests that P. aeruginosa adaptation to CF lung might result in a higher dependence on ErsA for the transduction of the multiple signals to the regulatory network of key functions for survivance in such a complex environment. Together, our results suggest that ErsA takes an upper place in the regulatory network of airways infection, transducing host inputs to biofilm-related factors, as underlined in our previous reports, and to functions that allow P. aeruginosa to thrive in low-oxygen conditions.